Adenosquamous carcinoma, a rare and unknown tumor - Benat Gauthier; Cros Alice; Sarini Jérôme; Galissier Thibault; Collins Francis; Laurencin-Dalicieux Sara; Cousty Sarah (EDP Sciences, 2018)
Introduction: Adenosquamous carcinoma (ASC) of the head and neck is a rare malignant tumor, with one hundred cases diagnosed so far in the literature. Observation: A 66 years old female patient had a ASC of the right posterior floor of the mouth with a classification T1N0M0. Treatment consisted of surgical management and active surveillance. Discussion: Through this case report, we present this type of tumor and we discuss the main differential diagnosis from a clinical and histological point of view. Conclusion: This entity was described for the first time in 1968 by Gerughty. The CAS is defined by the World Health Organization as "a tumor of the upper respiratory tract, with two distinct squamous and glandular components." The CAS is considered as an aggressive tumor with a redoubtable prognosis should not be ignored.